PENGARUH REBUSAN DAUN SALAM TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI KELURAHAN TELUK MAKMUR - Evi Evi; Raja Syafrizal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Hypertension is a form of chronic disease in the elderly. Physiological changes in the elderly indicate the need for another approach to treat hypertension, such as using herbal therapy. One form of herbal therapy that can be used to treat hypertension is bay leaves. Objective: to determine the effect of bay leaf decoction on reducing blood pressure in hypertensive patients in Teluk Makmur sub-district. Method: using descriptions with the application of nursing care the effect of bay leaf decoction on reducing blood pressure in hypertensive patients carried out in February 2023. The population was taken as many as 3 elderly people with hypertension who lived in Teluk Makmur Village. Respondents were given bay leaf boiled water twice a day for five days. Respondents' blood pressure was measured using a sphygmomanometer and an observation format. Results: From this study, during five days of morning and evening visits there was an effect of bay leaf decoction on reducing blood pressure in hypertensive patients in Teluk Makmur Village.Discusssion: That bay leaf cooking water has an effect on reducing blood pressure in hypertensive patients. Therefore, bay leaves can be used as a herbal therapy to reduce blood pressure in clients with hypertension.